IMPROVING MATHEMATICAL CONNECTION ABILITY THROUGH THE APPLICATION OF THE DISCOVERY LEARNING MODEL IN CLASS VIII OF SMP - Fatma Aulia; M. Duskri; Muhammad Yani (Jurnal Ilmiah Pendidikan dan Pembelajaran Matematika, 2023)
Mathematical connection skills are very important to be developed in students because they can develop new mathematical ideas in solving mathematical problems, can connect mathematical concepts, and can see and relate problems from various different points of view. Facts in the field show that the students' mathematical connection ability is still low. One alternative that is assumed to help improve mathematical connection skills is the application of the Discovery Learning model. The purpose of this study was to determine the improvement of students' mathematical connection abilities after the Discovery Learning model was applied as a whole and based on indicators of mathematical connection ability. The research method used was a quasi-experimental design with a Pretest-Postest Control Group Design with a sample class VIIIA and VIIIB. Class VIIIA as many as 25 students as the experimental class and class VIIIB as many as 23 students as the control class. Data were collected using a mathematical connection ability test which was then analyzed using independent t-test and n-gain. The results of the study were: (1) The improvement of students' mathematical connection ability was better after being taught with the Discovery Learning model; and (2) there was an increase in the students' mathematical connection ability after the application of the Discovery Learning model for each indicator, namely the ability to connect between mathematical concepts increased by 44%; the ability to relate mathematics to other disciplines increased by 28%; and the ability to relate mathematics to everyday life increased by 36%.Keywords: Discovery Learning Model, Mathematical connection ability